Exploring the perceived barriers of effective communication within the coach-athlete relationship: a sample of Scandinavian coaches and athletes - Davis, L.; Wachsmuth, S.; Jowett, S.; Räisänen, P.; Hajo, K.; Nordberg, N.; Sommer, M. (International Sport Coaching Journal, 2026)
Coaching is a process that guides development and is shaped by sound relationships between athletes and coaches. Interpersonal communication represents a mechanism for developing functional relationships. However, not all interactions between coaches and athletes are optimal, and limited research has attempted to understand the factors that impede the ability to engage in effective communication. This study aimed to contribute to the literature by exploring the barriers experienced by high-performance coaches and athletes that hinder interpersonal communication within the coach-athlete relationship. A qualitative design grounded in a pragmatic philosophical position was utilised, and 20 semistructured interviews with 12 coaches and eight athletes participating in elite team sports were carried out. Interviews were conducted either in person or digitally via an online platform and analysed through content analysis. Barriers were identified for either coaches, athletes, or both and categorised as follows: (a) intrapersonal (e.g., lack of skills and negative experiences), (b) interpersonal (e.g., lack of concern/interest and power imbalance), and (c) environmental factors (e.g., hierarchy and toxic culture). These results suggest efforts should be focused on equipping coaches and athletes with intra- and interpersonal skills and empowering them to co-create a safe and united culture for themselves and their sport.